2020
DOI: 10.1093/jxb/eraa345
|View full text |Cite
|
Sign up to set email alerts
|

N-hydroxypipecolic acid: a general and conserved activator of systemic plant immunity

Abstract: This article comments on: Schnake A, Hartmann M, Schreiber S, Malik J, Brahmann L, Yildiz I, von Dahlen J, Rose LE, Schaffrath U, Zeier J. 2020. Inducible biosynthesis and immune function of the systemic acquired resistance inducer N-hydroxypipecolic acid in monocotyledonous and dicotyledonous plants. Journal of Experimental Botany 71, 6444–6459.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Notably, activation of NPR1 through SA is dependent on the plant redox state ( Saleem et al., 2021 ). The perception of NHP still needs to be elucidated; as yet, no receptor has been identified ( Hartmann and Zeier, 2019 ; Guerra and Romeis, 2020 ). It was shown that despite structural similarities, NHP does not bind to NPR1 in vitro , while SA binds with a Kd of 585 ± 368 nM ( Nair, 2021 ).…”
Section: Naturally Occurring Priming Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, activation of NPR1 through SA is dependent on the plant redox state ( Saleem et al., 2021 ). The perception of NHP still needs to be elucidated; as yet, no receptor has been identified ( Hartmann and Zeier, 2019 ; Guerra and Romeis, 2020 ). It was shown that despite structural similarities, NHP does not bind to NPR1 in vitro , while SA binds with a Kd of 585 ± 368 nM ( Nair, 2021 ).…”
Section: Naturally Occurring Priming Processesmentioning
confidence: 99%
“…NHP and Pip are important endogenous plant immune modulators that possess priming activity ( Table 1 , Figure 2 ) when exogenously applied to various plants ( Guerra and Romeis, 2020 ). Pip pretreatment increased the resistance to bacteria, SA biosynthesis and camalexin production.…”
Section: Natural Chemical Priming Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR is associated with transcriptional changes in distal leaves that are dependent on two endogenous chemicals, salicylic acid (SA) and N-hydroxypipecolic acid (NHP) [4]. SA, biosynthesized by the isochorismate synthase (ICS) and phenylalanine ammonia lyase pathways, is a well-recognized key regulator of plant immunity to biotrophic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In dicotyledonous and monocotyledonous plants, enhanced disease resistance is very effective in suppressing infections caused by biological and semibiological vegetative pathogens ( Li et al, 2016 ). Many compounds have been identified as mobile signals of SAR, including salicylic acid ( Metraux et al, 1990 ), methyl salicylate, pipecolic acid (Pip) ( Ding et al, 2016 ), azelaic acid ( Vicente et al, 2012 ), glycerol-3-phosphate ( Chanda et al, 2011 ), nicotinamide adenine dinucleotide, N -hydroxy-pipecolic acid (NHP) ( Guerra and Romeis, 2020 ), nicotinamide adenine dinucleotide phosphate, and dehydroabietinal ( Chaturvedi et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%